Translation techniques of Indonesian children’s picture book: The Sacred Crocodile - Iin Inawati; Dian Savitri; Dian Rosawati Fitriani; Nita Listiyaningtyas (Universitas Ahmad Dahlan, 2022)
Translating a children's picture book is a challenging process. The focus of translating children's picture books is not only to transfer the meaning into the target language but also to guide the children to quickly understand the meaning of the sentences. Therefore, the translator must apply the appropriate sentence translation technique. This study aims to describe translation techniques used in translating Indonesian children's picture books into English. The data of this study are sentences taken from the Indonesian picture book